REDESAIN INTERIOR BANK PERKREDITAN RAKYAT ARTHA WIWAHA ARJUNA DI KABUPATEN MALANG - Anjar Listyanto Adhitama; I Dewa Gede Putra; Nyoman Gema Endra Persada (Jurnal PATRA, 2020)
Rural Bank is one of the banks that serve micro, small, and medium-sized entrepreneurs (MSMEs) in order to help MSMEs to advance the economy in Malang Regency. The rural bank that will be redesigned is Artha Wiwaha Arjuna with the aim of improving the interior and furniture to be more effective and efficient and renovating design to improve the performance of the rural bank. The process of collecting primary data is done by observation and interview and secondary data by finding information from reference sources. The data is analyzed with qualitative and quantitative methods, then adjusted to the themes and concepts to be redesigned. The conclusion obtained is rural bank must serve customers as much as possible, then rural bank must create a pleasant atmosphere for customers, one of which is to present an effective and efficient transaction experience and a visual interior experience that gives the impression of enthusiasm to both customers and staff. Keywords: rural bank, office layouting, services, effective, efficient, redesign, interior. BPR (Bank Perkreditan Rakyat) adalah salah satu bank yang melayani golongan pengusaha mikro, kecil, dan menengah (UMKM) agar dapat membatu UMKM untuk memajukan ekonomi di Kabupaten Malang. BPR yang akan diredesain adalah BPR Artha Wiwaha Arjuna dengan tujuan untuk memperbaiki ruangan dan furnitur agar lebih efektif dan efisien serta memperbarui desain sehingga meningkatkan kinerja BPR. Proses pengumpulan data primer dilakukan dengan cara observasi dan wawancara serta data sekunder dengan mencari informasi dari sumber referensi. Data tersebut kemudian dianalisa dengan metode kualitatif dan kuantitatif, kemudian disesuaikan dengan tema dan konsep yang akan diredesain. Kesimpulan yang diperoleh adalah BPR harus melayani nasabah dengan semaksimal mungkin, maka BPR harus membuat suasana yang menyenangkan kepada nasabah, salah satunya yaitu menghadirkan pengalaman bertransaksi yang efektif dan efisien dan pengalaman visual interior yang memberi kesan semangat kepada nasabah maupun staf. Kata Kunci: bank perkreditan rakyat, tata ruang kantor, pelayanan, efektif, efisien, redesain, interior.